2007
DOI: 10.3748/wjg.v13.i4.588
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of p53, cyclinD1, RB1, c-fos and N-ras gene expression in hepatocellular carcinoma in Iran

Abstract: AIM:To study the effect of some genes especially those involved in cell cycle regulation on hepatocellular carcinoma. METHODS:Paraffin-embedded tissue samples of 25 patients (18 males and 7 females) with hepatocellular carcinoma were collected from 22 pathology centers i n Te h ra n d u r i n g 2 0 0 0 -2 0 0 1 , a n d s t a i n e d u s i n g immunohistochemistry method (avidin-biotin-peroxidase) for detection of p53, cyclinD1, RB1, c-fos and N-ras proteins. RESULTS:Six (24%), 5 (20%), 12 (48%) and 2 samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…Cyclin D1 is a protein closely associated with cell proliferation, and it is mainly involved in the G1 phase of the cell cycle. It plays an extremely important role in the regulation of the cell cycle (Moghaddam et al, 2007). Our results suggested that dexamethasone significantly reduced PCNA and cyclin D1 expression, and with the reduction in cyclin D1 expression, mitotic complexes were not formed.…”
Section: Discussionmentioning
confidence: 67%
“…Cyclin D1 is a protein closely associated with cell proliferation, and it is mainly involved in the G1 phase of the cell cycle. It plays an extremely important role in the regulation of the cell cycle (Moghaddam et al, 2007). Our results suggested that dexamethasone significantly reduced PCNA and cyclin D1 expression, and with the reduction in cyclin D1 expression, mitotic complexes were not formed.…”
Section: Discussionmentioning
confidence: 67%
“…One study using immunohistochemical analysis demonstrated that c-FOS serves a key role in HCC pathogenesis (32). The upregulation of c-FOS and Jun proto-oncogene mediated by protein kinase R promotes HCC proliferation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated expression of EGF-R is a frequent finding in HCC [37][38][39] , and increased EGF-R signaling has been associated with a poorer prognosis [40] . c-Fos is also frequently overexpressed in HCC tumoral tissues [13][14][15]41] . Our data, therefore, suggest that a causal relationship could exist between c-Fos and EGF-R overexpression in HCC.…”
Section: Discussionmentioning
confidence: 99%